THE RATIONAL CHARACTER TABLE OF SPECIAL LINEAR GROUPS (Journal of Sciences, Islamic Republic of Iran)
In this paper we will give the character table of the irreducible rational representations of G=SL (2, q) where q= , p prime, n>O, by using the character table and the Schur indices of SL(2,q).